Inflammatory Cells in Atherosclerosis - Marcelle Mehu; Chandrakala Aluganti Narasimhulu; Dinender K. Singla (MDPI AG, 2022)
Atherosclerosis is a chronic progressive disease that involves damage to the intima, inflammatory cell recruitment and the accumulation of lipids followed by calcification and plaque rupture. Inflammation is considered a key mediator of many events during the development and progression of the disease. Various types of inflammatory cells are reported to be involved in atherosclerosis. In the present paper, we discuss the involved inflammatory cells, their characteristic and functional significance in the development and progression of atherosclerosis. The detailed understanding of the role of all these cells in disease progression at different stages sheds more light on the subject and provides valuable insights as to where and when therapy should be targeted.